Pedagogia da terra e a formação de professores para a educação do campo na UFS e UFRN - Meneses, Maria Adeilma (2009)
The demands for education, presented by social field movements, brought the education of the rural areas to discussion, from which it has created the National Program of Education in the Land reform, which has, in the last ten years, turned the access to superior level education possible for a piece of population that had never had the opportunity for entering the university. In this study, linked to the Group of Inquiry Education and Social Movements of the line of Inquiry History, Society and Education Thought of the Nucleus of Postgraduation on Education of Federal University of Sergipe, we analyze the curricular organization of tertiary education level courses in Teachers' Formation of the Field, in the Federal University of Rio Grande do Norte and in the Federal University of Sergipe. This work is characterized as a qualitative inquiry, a documentary type from historical sources, for which we opt for a historic materialist dialectic approach. This work draws the historical journey of the teachers' formation in Brazil and teachers' subsequent formation for education on field, with characteristics and own specificities inside the process of reconstruction of field identity as a differentiated space, however not reduced regarding the urban areas. Equally, this study tries to identify, in the projects of the courses, the theoretical bases that give it sustenance for the formation of these teachers since the beginnings of the proposal curricular and on basis of central categories of analysis, to know: emancipation and praxis. For this, we refer ourselves to works of Adorno (1995); Freire (1982, 2002); Triviños (2006); Freitas (1995); Mészáros (2005); Santos (2005); Arroyo (2005); Caldart (2002, 2004, 2008); Jesus (2005, 2006, 2008). By the study, we checked that proposals present a quite advanced conception of education, however it points out its limits in his institutionalization because such proposals need an institutional opening that s not real yet.